A New Criterion for the ESG Model - Gazman, Victor D. (Green and Low-Carbon Economy, 2023)
This article presents the results of the study, the purpose of which was to develop a new criterion for the Environment, Social, Governance (ESG) model and recommendations for its use in the ESG in determining the socioeconomic benefits of wind and solar energy instead of the most toxic generation—coal. The criterion proposed by the author for the ESG model has not been previously considered in the scientific literature. Based on the theoretical assumptions, the author’s methodology for determining the achieved savings is presented in the example of a number of large energy companies RWE, Enel, and Sunseap in Singapore. This article presents the model developed by the author and the calculations themselves and comments related to the proposed model. This article presents the author’s developed model and the calculations and comments themselves. The calculations carried out are based on the actual amount of carbon dioxide emissions charges, taking into account the damage caused, the number of people saved from premature death due to harmful CO2 emissions into the atmosphere, the value of statistical life determined by the WorldBank for Germany, Singapore, and Italy, the costs of treating concomitant diseases, and the social discount rate. This makes it possible to determine the real socioeconomic effect of replacing fossil energy sources with cleaner energy carriers that are not carbon-containing. An argument is presented that refutes the argument about the occurrence of a significant increase in costs in the economy that may arise due to the introduction of a fixed fee for harmful emissions. This allows you to set more accurate benchmarks and indicators in the ESG system and use them in attracting investors, forming ratings, and training specialists. The results of the research presented in this article may be useful for analysts who are engaged in the development and use of ratings for the ESG model, primarily for section E but also for section S. This article highlights the possibilities of accelerating invest. Received: 3 November 2022 | Revised: 2 January 2023 | Accepted: 5 January 2023 Conflicts of Interest The author declares that he has no conflicts of interest to this work.